Penguatan Ketahanan Nasional melalui Literasi Digital untuk Ibu-Ibu PKK dalam Menangkal Hoaks dan Radikalisme - Intan Cynara Valentina Putri; Rahmi Mudia Alti; Ike Yuni Wulandari; Elfitra Desifatma (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity was carried out with the aim of improving digital literacy for PKK women in RW 25 as an effort to strengthen family-based national resilience. This activity is a response to the phenomenon of the increasingly widespread hoaxes and radical content on social media that infiltrate and influence perceptions at the household level. This activity uses an educational-participatory approach in the form of workshops, simulations of fact-checking, and discussions on ethical social media use. This activity was attended by 36 participants in five main sessions and two follow-up sessions. The evaluation results show that there is a significant increase in understanding, with average scores increasing from 52.3 to 86.4 or 65%. In addition, five digital literacy agents were formed at the neighborhood level to become local facilitators. This program successfully builds critical awareness, ethical online behavior, and strengthens women's roles as guardians of national values in the digital era.